The Palgrave Handbook of the Psychology of Sexuality and Gender
XXIX, 505 p.
Keywords: The Palgrave Handbook of the Psychology of Sexuality and Gender combines cutting edge research to provide a thorough overview of all the normative - and many of the less common - sexualities, genders and relationship forms alongside psychological and intersectional areas relating to sexuality and gender.